ANALISIS ALOKASI BELANJA DESA TERHADAP PEMBANGUNAN DESA (STUDI KASUS DESA BERKEMBANG DI KABUPATEN TRENGGALEK TAHUN 2019-2022) - Prasetyawan, Muhammad Rafli Alan Retsa; Fadjar, Nurman Setiawan (Journal of Development Economic and Social Studies, 2023)
Village expenditure has an important role in increasing village development. To realize the Sustainable Development Goals (SDGs) program, villages need to support this program by actualize a good village development. The purpose of this research is to identify the effect of village expenditure allocations toward village development. The research model used in this research is panel data with cases in 36 developing villages in Trenggalek Regency in 2019-2022. Partially, this study resulted a significant positive relationship between village spending on development implementation and spending on community development toward village development. However, spending on village administration and spending on community empowerment has no influence to village development